A secondary ion mass spectrometry (SIMS) re-evaluation of B and Li isotopic compositions of Cu-bearing elbaite from three global localities - Ludwig, Thomas; Marschall, Horst R.; Strandmann, P. A. E. Pogge von; Shabaga, B. M.; Fayek, M.; Hawthorne, F. C. (Mineralogical magazine, 2011)
Cu-bearing elbaite from Paraíba (Brazil) is a highly-prized gem tourmaline. Specimens of similar quality from localities in Mozambique and Nigeria are being sold, and reliable provenance tools are required to distinguish specimens from the original locality from ‘Paraíba-type’ tourmaline from Africa. Here we present Li and B isotope analyses of Cu-bearing elbaite from all three localities and demonstrate the suitability of these isotope systems as a provenance tool. Isotopic profiles across chemically zoned grains revealed homogenous B and Li isotopic compositions, demonstrating a strong advantage of their application as a provenance tool as opposed to major, minor or trace element signatures.Li and B isotopes of all investigated samples of Cu-bearing elbaites from the three localities are within the range of previously published granitic and pegmatitic tourmaline. Anomalous isotope compositions published previously for these samples are corrected by our results.
Elektronische Reproduktion der Druck-Ausgabe
Gesehen am 11.11.2022